Pengaruh Debt To Asset Ratio Terhadap Laba Bersih Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 - 2017 - Riyadi, Wulan (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2019)
This study aims to determine whether Debt to Asset Ratio (DAR) has an effect on Net Profit in Food and Beverage companies that are listed on the Indonesia Stock Exchange in 2015 - 2017. The independent variable used is Debt to Asset Ratio and the dependent variable used is Net Profit . The method used in this research is descriptive and verification method. The population in this study is a Food and Beverage company listed on the Indonesia Stock Exchange. The sampling technique used in this study was purposive sampling technique where sampling techniques with certain criteria. From the predetermined criteria of the Company that meets the criteria of 12 companies listed on the Indonesia Stock Exchange in 2015 - 2017. The analytical tool used in this study is simple regression analysis and hypothesis testing in this study using a computer-assisted t test, the SPSS Version 21.0 for Windows. The results of this study indicate that the Debt to Asset Ratio has a positive and significant effect on Net Profit. The results of the hypothesis test indicate that the proposed hypothesis can be verified.